Chip formation and coefficient of friction in turning S45C medium carbon steel - A. Raof, Natasha; Othman, Hazreen; A. Ghani, Jaharah; Che Haron, Che Hassan; Junaidi, Syarif (International Journals of Engineering and Sciences Publisher, 2014)
This paper presents the tribology issue regarding the chip formation in machining medium carbon steel (S45C) using coated and uncoated carbide tool. The machining parameters under investigation were cutting speed, feed rate, and depth of cut under dry cutting condition using coated and uncoated carbide tools. The chip shape was largely depends on the combination of machining parameters especially at high depth of cut, the favorable chips was produced. Smaller value of coefficient of friction indicates that the shear angle is larger which results in smaller shear plane area that provides benefits of lower cutting force needed to shear off the chips and lower cutting temperature being generated during the machining process.